Genome‐wide analysis of the callose enzyme families of fertile and sterile flower buds of the Chinese cabbage (Brassica rapa L. ssp. pekinensis). Issue 8 (12th July 2019) - Pu, Yanan; Hou, Lingyun; Guo, Yingqi; Ullah, Ikram; Yang, Yongping; Yue, Yanling
Abstract : Callose is a β‐1, 3‐glucan commonly found in higher plants that plays an important role in regulating plant pollen development. It is synthesized by glucan synthase‐like (GSL) and is degraded by the enzyme endo‐1, 3‐β‐glucosidase. However, genome‐wide analyses of callose GSL and endo‐1, 3‐β‐glucosidase enzymes in fertile and sterile flower buds of Chinese cabbage have not yet been reported. Here, we show that delayed callose degradation at the tetrad stage may be the main cause of microspore abortion in Chinese cabbage with nuclear sterility near‐isogenic line '10L03'. Fifteen callose GSLs and 77 endo‐1, 3‐β‐glucosidase enzymes were identified in Chinese cabbage. Phylogenetic, gene structural and chromosomal analyses revealed that the expansion occurred due to three polyploidization events of these two gene families. Expression pattern analysis showed that the GSL and endo‐1, 3‐β‐glucosidase enzymes are involved in the development of various tissues and that the genes functionally diverged during long‐term evolution. Relative gene expression analysis of Chinese cabbage flowers at different developmental stages showed that high expression of the synthetic enzyme BraA01g041620 and low expression of AtA6 ‐homologous genes ( BraA04g008040, BraA07g009320, BraA01g030220 and BraA03g040850 ) and two other genes ( BraA10g020080 and BraA05g038340 ) for degrading enzymes in the meiosis and tetrad stages may cause nuclear sterility in the near‐isogenic line '10L03'. Overall, our data provide an important foundation for comprehending the potential roles of the callose GSL and endo‐1, 3‐β‐glucosidase enzymes in regulating pollen development in Chinese cabbage. Abstract : Flower buds samples from Chinese cabbage of fertile and sterile were analyzed by paraffin sections, light microscopy and genome‐wide. Relative gene expression analysis showed that high expression of a synthetic enzyme and low expression of six degrading enzymes in the meiosis and tetrad stages may cause nuclear sterility in the near isogenic line '10L03'.